The landscape spreads as far as you can feel it. An atmospheric liminology (Lebenswelt. Aesthetics and philosophy of experience., 2024)
My hypothesis is that landscape is identified by the atmospheric feeling it radiates in a now constant and now more ephemeral way and by the felt-bodily resonance it generates in those who simply perceive it, and a fortiori in those who are also deeply affectively grasped by it. In partial contrast to a reductionist approach prevalent today, the intention is to demonstrate that the (feeling of) landscape, in its constitutive extraneousness to the objective-quantitative dimension, can never be fully explained in pragmatist and socio-constructivist terms. In fact, it holds and even enhances its critical role if its fundamental affordance remains that of allowing a ‘contemplative’ (in the broadest sense) perspective, i.e. a involuntary, distanced, supervenient as well as ‘framed’ by boundaries perception. Precisely in questioning its boundaries, how it extends exactly as far as you feel its inherent atmosphere, the paper sketches in conclusion a liminology of the landscape on an atmospherological basis.